Presepsi Guru dalam Penerapan Konsep Pendidikan Merdeka Belajar di SMP Negeri 31 Halmahera Barat - Syarifuddin Adjam; Fitriana Ibrahim; Ningsi Saibi; Asnita Ode Samili; Jainudin Hasim (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the teacher's perception and implementation of the concept of Independent Learning at SMP Country 5 Ternate City. This research is a qualitative type that uses data collection techniques in the form of open questionnaires and literature studies. The research subjects were junior high school teachers and various literature sources regarding Merdeka Learning. The results showed that: (1) respondents had various perceptions about the concept of Merdeka Learning, which can be described as follows: the majority of junior high school teachers understand Merdeka Learning as a policy that only contains the abolition of the National Examination and the concept of learning without being burdened by score achievements, almost half of junior high school teachers understand Merdeka Learning as an educational innovation concept that gives freedom to develop the potential of teachers and students in the teaching and learning process without going through the legal signs of education in Indonesia and a minority of junior high school teachers who do not know about the concept of implementing Merdeka Learning; (2) Merdeka Learning is considered a good policy and needs to be tried to improve the quality of education in Indonesia, they hope that the government can optimize the socialization, piloting and dissemination stages of the implementation of Merdeka Learning.